Proyeksi kebutuhan lahan padi sawah dan evaluasi kesesuaian lahan padi sawah dalam mencukupi kebutuhan pangan di provinsi Papua Barat - Bernadus Yulino; Samsul Bachri; Siti Hadjar Kubangun; Irnanda A. F. Djuuna (Fakultas Pertanian Universitas Papua, 2019)
This study aimed to predict the need for lowland rice land, and evaluate the suitability of the land to meet food needs in the West Papua province. This study used a descriptive method with food demand projection techniques to predict the need for lowland rice land; and the technique of matching data on physical characteristics of land with land suitability criteria for lowland rice plants based on the Land Evaluation Technical Manual to evaluate the suitability of lowland rice fields. The projection result showed that the demand for food and land tends to increase every year, therefore, based on the comparison between food needs and the production, the West Papua province tends to experience a food deficit. An alternative to increase rice production is the extensification of paddy fields. The results of the evaluation of actual land suitability for lowland rice in the West Papua province ranged from the suitability class moderately suitable (S2) to marginally suitable (S3), with the limiting factor in the S2 land suitability class were nutrient retention (KB, CEC), available nutrients ( P2O5, N-total) and soil texture; while the limiting factors in the S3 land suitability class were slope, temperature and soil texture. If improvement efforts are made by adding organic matter and fertilization, then the distribution of potential land availability (available and suitable) is spread in very suitable land suitability classes (S1) and quite suitable (S2), with the largest land area being in Teluk Bintuni district.